2017
DOI: 10.1007/s00170-016-9876-6
|View full text |Cite
|
Sign up to set email alerts
|

The development of a Human Factors Readiness Level tool for implementing industrial human-robot collaboration

Abstract: The concept of industrial human-robot collaboration (HRC) is becoming increasingly attractive as a means for enhancing manufacturing productivity and product. However, due to traditional preventive health and safety standards, there have been few operational examples of true HRC, so it has not been possible to explore the organisational human factors that need to be considered by manufacturing organisations to realise the benefits of industrial HRC until recently. Charalambous, Fletcher and Webb (2015) made th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Yet, additional case studies that verify the identified factors in different organizational contexts are necessary. In a follow-up study [ 17 ], the authors developed the so-called human factors readiness level (HFRL) tool, which provides a guideline on how to make use of the identified enablers and barriers in practice. Both studies make clear that for HRC to be successful in practice, it is absolutely necessary to consider human factors throughout the whole implementation process.…”
Section: Acceptance Of Human-robot Interactionmentioning
confidence: 99%
“…Yet, additional case studies that verify the identified factors in different organizational contexts are necessary. In a follow-up study [ 17 ], the authors developed the so-called human factors readiness level (HFRL) tool, which provides a guideline on how to make use of the identified enablers and barriers in practice. Both studies make clear that for HRC to be successful in practice, it is absolutely necessary to consider human factors throughout the whole implementation process.…”
Section: Acceptance Of Human-robot Interactionmentioning
confidence: 99%
“…Indeed, continually informing employees would help reduce resistance to change [44]. This includes communication with unions and their inclusion into the process [45].…”
Section: Figure 1 Classification By Publication Datesmentioning
confidence: 99%
“…This will require greater attention to safety features when choosing the robots and the integration of health and safety management practices [13,46]. Ultimately, the work that addressed managerial implication the most specifically comes from Charalambous and his collaborators [8,45]. They emphasize the importance of employee inclusion and empowerment, top-down communication and active involvement from senior management.…”
Section: Figure 1 Classification By Publication Datesmentioning
confidence: 99%
“…One measure to quantify this spread is Technological Readiness Level (TRL), which is defined on a scale from one to nine [55]. In this thesis, research activities were directed towards TRL levels of less than six, which refers to demonstration of systems/subsystems in a relevant environment [55,56].…”
Section: Research Orientationmentioning
confidence: 99%